1967
DOI: 10.1128/aem.15.4.899-906.1967
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Laboratory Hazard of Bearded Men

Abstract: An investigation was conducted to evaluate the hypothesis that a bearded man subjects his family and friends to risk of infection if his beard is contaminated by infectious microorganisms while he is working in a microbiological laboratory. Bearded and unbearded men were tested with Serratia marcescens and Bacillus subtilis var. niger. Contact aerosol transmission from a contaminated beard on a mannequin to a suitable host was evaluated with both Newcastle disease virus and Clostridium botulinum toxin, type A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…A study of bearded microbiology laboratory personnel showed that bearded individuals retained bacteria sprayed onto their faces for longer than clean‐shaven colleagues [14]. In addition, the bacteria were more difficult to remove from the faces of the bearded individuals despite vigorous washing.…”
Section: Discussionmentioning
confidence: 99%
“…A study of bearded microbiology laboratory personnel showed that bearded individuals retained bacteria sprayed onto their faces for longer than clean‐shaven colleagues [14]. In addition, the bacteria were more difficult to remove from the faces of the bearded individuals despite vigorous washing.…”
Section: Discussionmentioning
confidence: 99%
“…[14] A study conducted on microbiology personnel where aerosolized bacteria were sprayed on bearded and clean-shaven men showed that bearded individuals retained the bacteria on their faces longer than their clean-shaven counterparts. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[14] A study conducted on microbiology personnel where aerosolized bacteria were sprayed on bearded and cleanshaven men showed that bearded individuals retained the bacteria on their faces longer than their clean-shaven counterparts. [15] The role of surgical facemasks (SFMs) in the operating room and the prevention of SSI remains controversial. [16][17][18] Tunevall et al conducted a randomized study in which 1537 operations were performed with masks with 4.7% SSI and 1551 operations were performed without a facemask with 3.5% SSI, with no statistical significance between the groups.…”
Section: Discussionmentioning
confidence: 99%